Hubungan antara kekuatan, koordinasi, dan keseimbangan dengan layanan underhand pada remaja pemain bola voli amatir - Destriana, Destriana; Muslimin, Muslimin; Yusfi, Herri; Anggraini, Putri (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
This study aimed to the contribution of arm muscle power to the underhand carrier, coordination of hand-eye to the underhand carrier, and stability of the underhand carrier inside the volleyball sport in contributors of Senior High School Muhammadiyah three Palembang. The type of research is quantitative with a correlation design and uses a sampling technique changed into a sampling method. In contrast, all participants of the populace were used as samples, totaling fifty-eight, including 31 guys and 27 women. A push-up test measures instruments. Arm muscle strength and coordination are measured using eye and hand coordination instruments, balance is measured using a Dynamic balance test, and an underhand serve test is used to determine volleyball underhand serve. Data analysis techniques using simple and multiple correlation tests and correlation assessments at the SPSS Model 26 program. The research results show the correlation between arm muscle strength, hand-eye coordination, balance, and underhand serve from a significant value of 0.00, and the value of R = 0.921 is perfectly correlated. This study suggests the contribution of arm muscle power, eye-hand coordination, and stability to floor carrier in volleyball in students.